The MORABIT approach to runtime component testing - Suliman, Dima; Paech, Barbara; Borner, Lars (30th Annual International Computer Software and Applications Conference, 2006)
Runtime testing is important for improving the quality of software systems. This fact holds true especially for systems which cannot be completely assembled at development time, such as mobile or ad-hoc systems. The concepts of built-in-test (BIT) can be used to cope with runtime testing, but to our knowledge there does not exist an implemented infrastructure for BIT. The MORABIT project realizes such an infrastructure and extends the BIT concepts to allow for a smooth integration of the testing process and the original business functionality execution. In this paper the requirements on the infrastructure and our solution are presented.